MANUFACTURING SELF-CHARGING POWERBANK DENGAN SUMBER HYBRID - Jody Adinugroho (2022)
The era of society 5.0 is currently making technology for everyday life continue to develop, such as handphones and portable electrical equipment. Handphones and portable electrical equipment can only function when the stored power is still there, so a powerbank is made to function as backup power. In this final project, we want to design and manufacture a selfcharging powerbank with the Electromagnetic method combined with external efforts in the form of kinetic energy. The powerbank of this project produces the following specifications: size 140x85x40mm, case material Polylactic Acid (PLA), capacity 6000mAh, input 5V/1A, and output average 3.1V/1.9A. The charging time for a power bank with a capacity of 6000mAh is 3.32 hours. And the costs spent on making a powerbank amounted to Rp. 314,500.